NIR-transparent dark paints based on diketopyrrolopyrrole pigments for LiDAR-enabled automobiles - Yu, Sung Ho; Lim, Taeho; Baek, Kyung-Youl; Sung, Myung Mo; Kim, Young-Seok; Cho, Sangho (한국고분자학회, 2023)
Recently, light detection and ranging (LiDAR) technology is being used in autonomous vehicles. The LiDAR emits a laser in the near-infrared (NIR) region and receives light reflected from the object to measure the distance and structure. However, the current dark-tone pigment is based on carbon black, so it absorbs not only visible light but also NIR, making it difficult to sense in LiDAR. We have developed a dark-tone paint bilayer structure that can reflect NIR. To achieve effective penetration within the near-infrared (NIR) spectrum, while simultaneously absorbing visible light, a novel set of diketopyrrolopyrrole (DPP) derivatives were synthesized and blended with yellow and blue organic pigments. This resulted in the production of a dark-tone pigment that was subsequently applied to layers possessing high levels of NIR reflectivity. As a result, we made a black pigment close to carbon black under Br-phenyl-DPP:Yellow151:CuPc = 1:1:3 conditions (L* = 27.0, a* = - 0.03, and b* = 0.35), and secured a high NIR reflectivity of 58.07% and good ultraviolet resistance (& UDelta;E = 0.29). We expect this result to be used as a dark-tone pigment applicable to LiDAR.Graphical abstractIn this study, we mixed three different organic pigments to develop an NIR-transparent dark-tone pigment. And this dark-tone pigment is coated on the NIR-reflective layer to construct NIR-reflective dart-tone bilayer. As a result, we fabricated the black color (L* = 27.0, a* = - 0.03, and b* = 0.35) with high NIR reflectivity (58.07%) and also good ultraviolet resistance (& UDelta;E = 0.29)